Effect of the Reciprocal Trade Agreements Upon the Foreign Trade of the United States - Beckett, Grace (Quarterly Journal of Economics, 1940)
Obstacles to statistical evaluation, 80. — Several types of measurement used: proportion of world trade transacted by the United States, 82; proportion of our trade with agreement and non-agreement countries, 84; analysis of exports and imports, 86; trade in concession and non-concession products, 90. — Trade with Canada as illustrative of first part of the period, 91. — Trade with other agreement countries as illustrative of second part of the period, 92. — Reasons for the results found, 93. — Probable effects, 94.